Principal Instructional Leadership in Building a Religious School Culture for Students’ Character Development - Farwati, Wiwik Wida (Al-Qalam Institue, 2025)
This study examines how instructional leadership enacted by madrasah principals strengthens students’ religious character in Islamic primary education. The erosion of religious values among students in the context of globalization and digital culture presents a critical challenge for Islamic schools. Prior studies indicate that character education initiatives often remain fragmented and insufficiently integrated into school culture. This research employed a qualitative case study design at MI Hamzanwadi NW Gelogor, utilizing semi-structured interviews, observations, and document analysis. Data were analyzed through data condensation, display, and verification to ensure analytical rigor. The findings indicate that strengthening religious character begins with participatory program planning informed by contextual needs and collective teacher involvement. Exemplary leadership practices, particularly the principal’s direct engagement in daily religious activities, serve as a key mechanism for internalizing values. Continuous supervision and reflective evaluation further support program sustainability and teacher commitment. These interconnected practices foster a coherent religious school culture that embeds Islamic values into students’ everyday experiences. The study contributes theoretically by framing religious character education as an organizational process mediated by instructional leadership and offers practical guidance for strengthening leadership capacity in Islamic schools. Future research is recommended to employ comparative and longitudinal designs across diverse educational contexts.